Occurrence and prevention of Pickering foams in pharmaceutical nano-milling - Lehocký, Róbert; Pěček, Daniel; Saloň, Ivan; Štěpánek, František (European journal of pharmaceutics and biopharmaceutics, 2019)
Particle size reduction to sub-micrometer dimensions in stirred media mills is an increasingly common formulation strategy used for improving the bioavailability of poorly aqueous soluble active pharmaceutical ingredients (APIs). Due to their hydrophobic character, the API particles need to be stabilised by a surfactant in order to form a stable nano-suspension. This work is concerned with the understanding of an undesired phenomenon often encountered during the development and scale-up of wet nano-milling processes for hydrophobic APIs - the formation of foams. We investigate the microstructure, rheology and stability of these foams, and find them to be Pickering foams stabilised by solid particles at the gas-liquid interface rather than by a surfactant. By exploring the effect of surfactant concentration on the on-set of foaming in conjunction with the milling kinetics, we find a relationship between the specific surface area of the nano-suspension, the quantity of surfactant present in the formulation and the occurrence of foaming. We propose a mechanistic explanation of foam formation, and find that in order to prevent foaming, a large surfactant excess of approx. 100x above the critical micelle concentration has to be present in the solution in order to ensure a sufficiently rapid coverage of freshly exposed hydrophobic surfaces formed during the wet nano-milling process.
Keywords: roztoky; Nanoparticles; povrchově aktivní látky; Solutions; Hydrophobic and Hydrophilic Interactions; Surface-Active Agents; biologická dostupnost; Specific surface area; Stabilisation; Surfactant; Suspensions; velikost částic; suspenze; Biological Availability; Technology, Pharmaceutical; Pickering foam; nanočástice; Nano-suspension; Nano-milling; farmaceutická technologie; Particle Size; hydrofobní a hydrofilní interakce